2021
DOI: 10.1111/pbi.13735
|View full text |Cite
|
Sign up to set email alerts
|

The chromosome‐scale genomes of Dipterocarpus turbinatus and Hopea hainanensis (Dipterocarpaceae) provide insights into fragrant oleoresin biosynthesis and hardwood formation

Abstract: Summary Dipterocarpaceae are typical tropical plants (dipterocarp forests) that are famous for their high economic value because of their production of fragrant oleoresins, top‐quality timber and usage in traditional Chinese medicine. Currently, the lack of Dipterocarpaceae genomes has been a limiting factor to decipher the fragrant oleoresin biosynthesis and gain evolutionary insights into high‐quality wood formation in Dipterocarpaceae. We generated chromosome‐level genome assemblies for two representative D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
21
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 84 publications
3
21
1
Order By: Relevance
“…3A ). The comparison of collinearity within the cotton genome and between the V. mangachapoi and cotton genomes both identified a large number of collinear blocks, consistent with the finding that cotton has undergone a WGD event 54 ( Supplementary Figs S3 and S4 ). The distribution of Ks within a genome can be used to detect WGD and estimate the time of such an event.…”
Section: Resultssupporting
confidence: 79%
See 3 more Smart Citations
“…3A ). The comparison of collinearity within the cotton genome and between the V. mangachapoi and cotton genomes both identified a large number of collinear blocks, consistent with the finding that cotton has undergone a WGD event 54 ( Supplementary Figs S3 and S4 ). The distribution of Ks within a genome can be used to detect WGD and estimate the time of such an event.…”
Section: Resultssupporting
confidence: 79%
“…A shared WGD event between D. turbinatus and H. hainanensis Chun was reported, and WGD in the common ancestor of Dipterocarpaceae was suggested. 54 The WGD detected in V. mangachapoi is likely the indication of WGD in the common ancestor of the three species. However, the timing of the WGD based on Ks plot analyses of V. mangachapoi genome is much younger than the time estimated in Wang et al 54 and deserve further investigation.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Polyploidization has long been regarded as an important driving force for plant evolution, and it may endow genes with potential sub‐functionalization and neo‐functionalization (Wang et al ., 2021). By performing KEGG enrichment on the α‐event‐related genes (duplicated by the α event and retained) obtained based on the median Ks value, we found that genes related to ascorbate and aldarate metabolism, lipid biosynthesis, and fatty acid elongation were significantly enriched, which coincided with the fact that seabuckthorn fruits were rich in AsA and fatty acids (Table S35).…”
Section: Resultsmentioning
confidence: 99%